A novel Lidar Ceilometer : design, implementation and characterisation - Vande Hey, Joshua D. (Cham, Switzerland : Springer, 2015)
A novel lidar ceilometer prototype based on divided lens optics has been designed, built, characterised and tested. The primary applications for this manufacturable ground-based sensor are the determination of cloud base height and the measurement of vertical visibility. First, the design, which was developed in order to achieve superior performance at a low cost, is described in detail, along with the process used to develop it. The primary design considerations of optical signal-to-noise ratio, range-dependent overlap of the transmitter and receiver channels and manufacturability, were balanced to develop an instrument with good signal-to-noise ratio, fast turn-on of overlap for detection of close range returns, and a minimised number of optical components and simplicity of assembly for cost control purposes. Second, a novel imaging method for characterisation of transmitter-receiver overlap as a function of range is described and applied to the instrument. The method is validated by an alternative experimental method and a geometric calculation that is specific to the unique geometry of the instrument. These techniques allow the calibration of close range detection sensitivity in order to acquire information prior to full overlap. Finally, signal processing methods used to automate the detection process are described. A novel two-part cloud base detection algorithm has been developed, which combines extinction-derived visibility thresholds in the inverted cloud return signal with feature detection on the raw signal. In addition, standard approaches for determination of visibility based on an iterative far boundary inversion method, and calibration of attenuated backscatter profile using returns from a fully attenuating water cloud, have been applied to the prototype. The prototype design, characterisation and signal processing have been shown to be appropriate for implementation into a commercial instrument. The work that has beeen carried...
Doctoral Thesis accepted by Loughborough University, UK
Thesis (doctoral)--Loughborough University, 2015
También en formato EPUB
Keywords: INGENIERÍA ÓPTICA; SENSORES; LASERS; FOTÓNICA; OPTICA; VIGILANCIA AMBIENTAL; GEOFISICA